2024
DOI: 10.3390/toxins16020103
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pulmonary Damage in Surviving Antitoxin-Treated Mice following a Lethal Ricin Intoxication

Yoav Gal,
Anita Sapoznikov,
Shlomi Lazar
et al.

Abstract: Ricin, a highly potent plant-derived toxin, is considered a potential bioterrorism weapon due to its pronounced toxicity, high availability, and ease of preparation. Acute damage following pulmonary ricinosis is characterized by local cytokine storm, massive neutrophil infiltration, and edema formation, resulting in respiratory insufficiency and death. A designated equine polyclonal antibody-based (antitoxin) treatment was developed in our laboratory and proved efficacious in alleviating lung injury and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The damage to the lung that we observed during the early time points post-sublethal exposure, included marked interstitial pneumonia, neutrophil infiltration, pro-inflammatory cytokine response, alveolar macrophage and alveolar epithelia type II cell death and edema. These observations stand in line with previous studies, where a lethal dose was used by intranasal instillation 8 , 9 , 28 , 29 , 35 , 36 , which also corresponded with other studies in rodents following inhalation exposure 34 , 42 , 43 . Altogether, our findings further substantiate intranasal instillation as a solid alternative respiratory exposure route for ricin intoxication in mice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The damage to the lung that we observed during the early time points post-sublethal exposure, included marked interstitial pneumonia, neutrophil infiltration, pro-inflammatory cytokine response, alveolar macrophage and alveolar epithelia type II cell death and edema. These observations stand in line with previous studies, where a lethal dose was used by intranasal instillation 8 , 9 , 28 , 29 , 35 , 36 , which also corresponded with other studies in rodents following inhalation exposure 34 , 42 , 43 . Altogether, our findings further substantiate intranasal instillation as a solid alternative respiratory exposure route for ricin intoxication in mice.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, a new study evaluated the long-term pulmonary damage (30 days post-exposure) in surviving anti-ricin antibody-treated mice following a lethal ricin intoxication. This study showed evidence of lung fibrosis, hyperpermeability and decreased lung compliance 35 . In majority of these studies that aimed to understand the outcomes of sublethal exposure to ricin, the efforts were focused on the short-time period post exposure, the acute phase of the disease with merely evaluation of the long-term toxicity of ricin.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation